Andean region policies in planning and management of human resources in health - Núñez, Manuel (2015)
The countries of the Andean subregion Bolivia, Chile, Colombia, Ecuador, Peru and Venezuela, integrated into the Andean Health Organization - Hipólito Unanue Convention (ORAS - CONHU) developed and approved by Resolution REMSAA XXXIII / 474 of 23 November 2012, Andean Policy Planning and Management of Human Resources in Health and implementation of its Action Plan 2013-2017.